The Role of Mosques as Centers for Education and Islamic Entrepreneurship Incubation in Ternate - Abdurrahman Hi. Usman; Kartika Fitriyanti Salman; Reny Hi. Lut; Santi Muhammadun; Ardian Kader; Abdullah Abubakar (Electronic Journal of Education, Social Economics and Technology, 2025)
Mosques have strategic potential as centers for empowering the community economically, but in practice, this function has not been fully optimized. This research aims to analyze the role of mosques as centers of Islamic education and entrepreneurial incubation in Ternate City, as well as to identify supporting factors, obstacles, and their impact on the well-being of the congregation. This research uses a qualitative approach with a case study design, conducted at several mosques in Ternate City that have implemented economic empowerment programs. Data was collected thru in-depth interviews, participant observation, focus group discussions, and document studies, and then analyzed using the interactive model of Miles and Huberman. The research findings indicate that mosques in Ternate City have begun to play a role in Islamic entrepreneurship education and micro-business mentoring for congregants, particularly thru strengthening Islamic business ethics values, utilizing religious social funds, and establishing mosque-based social networks. However, its implementation is still limited, unstructured, and faces constraints in terms of human resources, governance, and institutional collaboration. This research concludes that optimizing the role of mosques as centers of Islamic education and entrepreneurial incubation requires an integrated, professional, and contextual approach to sustainably improve the well-being of the congregation.